Potential Coconut Coir Fiber as Soil Reinforcement - Razali, Mohd Aris; Yahya, Nur Faezah; Tuan Ismail, Tuan Noor Hasanah (Progress in Engineering Application and Technology, 2020)
Coconut coir fibre (CCF) is one of the natural fibres abundantly available in tropical regions, and is extracted from the husk of coconut fruit. Coconut coir fibre will be used as reinforcement material meanwhile to reduce waste material and save environment. This research will evaluate the effect of load on the tensile properties of coconut coir fibre using different diameter 0.2,0.3,0.4,0.5 and 0.6 mm with same length 0.7 mm and tensile test will be carried out to determine the properties of coconut coir fibre. The research carried out and the conclusions drawn by different researchers in last few decades are also briefly presented. Graphs showing the relationship between different properties are also shown in this paper. The ultimate tensile strength value base on graph have been obtain with 0.2 mm  2.86,286.08, 0.3 mm 44,23,0.4 mm 6.47,87.41,  0.5 mm 28.57,85.46 and 0.6mm  41.93,88.3 and fracture is 0.2 mm 36, 0.3 mm 92, 0.4 mm 44, 0.5 mm 68 and 0.6 mm 108. The high ultime tensile strength and fracture, that can conclude  the higher diameter is suitable for reinforement material. The diameter of CCF will affect on strength of the reinforcement. Coconut fibres reinforced composites have been used as cheap and durable non-structural elements. The aim of this review is to spread awareness of coconut fibres as a construction material in civil engineering.